INFLASI SEBAGAI VARIABEL MODERASI PADA PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH TANGERANG SELATAN - Dila Angraini; Gyta Fitriandryany (Universitas Dian Nuswantoro, 2022)
This study aims to determine the effect of local taxes and levies on local revenue with a moderating variable, namely inflation in the city of South Tangerang in 2011-2020. The type of research used is quantitative by using data collection methods using secondary data. The sampling technique used is the saturated sample method, namely the method of determining the sample with the entire population as the research sample. The population in this study is the city of South Tangerang in 2011-2020. The results of the study prove that simultaneously and partially local taxes and regional levies have a positive and significant effect on local revenue. While inflation is not a moderating variable on the effect of local taxes and regional levies on local revenue